The Rohingya crisis: a legal analysis of human rights violations and the responsibility to protect - Auziņš, Emīls (Riga Graduate School of Law, 2024)
The aim of this thesis is to find to what extent the actions and policies surrounding the Rohingya crisis constituted violations of international human rights law, international criminal law and other forms of international law. It also seeks to analyse the response of the international community to the Rohingya crisis under the framework of the responsibility to protect. The author found substantial evidence of several violations of international law under the Genocide Convention and Rome Statute. The responsibility to protect norm has largely failed in Myanmar, due to a delayed response, insufficient measures and its necessity for UNSC authorisation. However, members of the international community have, to varying degrees of success, enacted measures to promote accountability and protect the Rohingya people.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::International law; Human rights law; Responsibility to Protect; Crimes Against Humanity; Genocide